2023
DOI: 10.1172/jci.insight.169020
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania major drives host phagocyte death and cell-to-cell transfer depending on intracellular pathogen proliferation rate

Iris Baars,
Moritz Jaedtka,
Leon-Alexander Dewitz
et al.

Abstract: The virulence of intracellular pathogens relies largely on the ability to survive and replicate within phagocytes but also on release and transfer into new host cells. Such cell-to-cell transfer could represent a target for counteracting microbial pathogenesis. However, our understanding of the underlying cellular and molecular processes remains woefully insufficient. Using intravital 2-photon microscopy of caspase-3 activation in the Leishmania major –infected ( L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Since Carneiro et al (2020) showed upregulation of IL1β during this phase of the infection, it is tempting to speculate that pyroptosis might play a role in the spread of parasites to new host cells. However, it has been recently demonstrated that the cell-to-cell spread of L. major can be driven by the parasites proliferation and the induction of apoptosis (Baars et al, 2023;Heyde et al, 2018). Interestingly, transcriptomic profiling of tissue from lesions of cutaneous leishmaniasis patients infected with L. braziliensis revealed an upregulation of inflammasome as well as apoptosisassociated genes, suggesting the activation of both pathways during leishmaniasis (Novais et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Since Carneiro et al (2020) showed upregulation of IL1β during this phase of the infection, it is tempting to speculate that pyroptosis might play a role in the spread of parasites to new host cells. However, it has been recently demonstrated that the cell-to-cell spread of L. major can be driven by the parasites proliferation and the induction of apoptosis (Baars et al, 2023;Heyde et al, 2018). Interestingly, transcriptomic profiling of tissue from lesions of cutaneous leishmaniasis patients infected with L. braziliensis revealed an upregulation of inflammasome as well as apoptosisassociated genes, suggesting the activation of both pathways during leishmaniasis (Novais et al, 2015).…”
Section: Discussionmentioning
confidence: 99%